Distribuição potencial e revisão do status de conservação de duas espécies de anfíbios endêmicos: Scinax cabralensis e Bokermannohyla sagarana - Laila Mascarenhas Pimenta (2016)
Habitat loss and fragmentation are the main causes of species extinctions. Changes in land use lead to global environmental impacts and are mostly caused by humans. Many species are likely to become extinct in a few years, especially those that are endemic and occupy specific habitats. For species with restricted distribution, such as Scinax cabralensis and Bokermannohyla sagarana, endemic from the Serra do Cabral, in the southeastern of Brazil, habitat loss is likely to be the main cause of population decline and vulnerability to extinction. Species withsimilar attributes should be focused for conservation because their small range makes them more vulnerable to extinction due to decreases in genetic diversity, demographic stochasticity and environmental fluctuations. The Serra do Cabral is under pressure from illegal fires, cattle ranching and changes in land cover with Eucalyptus and Pinus plantations replacing native vegetation. All these changes are expected to decrease local biodiversity, and the assessment of their impacts is of utmost importance to assess the likelihood of species permanence. Thisthesis aims to provide baseline data for effective protection planning of two endemic frog species from the Serra do Cabral, analyzing to what extent land cover affects their distribution. Models of environmental suitability were generated using the software Maxent and climatic/topographic data. Vegetation was included as an additional variable in a second model. Habitat loss was estimated as the area covered by silviculture subtracted from the area predicted as suitable by the model without the variable vegetation. Habitat loss was 10,99%for S. cabralensis and 10,58% for B. sagarana. The model including vegetation cover showed only 15.16% of the predicted suitable area for Scinax cabralensis to be protected within the only a conservation unit at the region, as well as only 16.75% of the suitable area for Bokermannohyla sagarana. Given the above mentioned, propose changes in the conservation status of the Scinax cabralensis in the IUCN red list.